Electronic‐Grade High‐Quality Perovskite Single Crystals by a Steady Self‐Supply Solution Growth for High‐Performance X‐ray Detectors. Issue 33 (6th July 2020) - Wang, Wenzhen; Meng, Hua; Qi, Huanzhen; Xu, Haitao; Du, Wenbin; Yang, Yiheng; Yi, Yongsheng; Jing, Shengqi; Xu, Shanhu; Hong, Feng; Qin, Juan; Huang, Jian; et al.
Abstract: High‐quality perovskite single crystals with large size are highly desirable for the fundamental research and high energy detection application. Here, a simple and convenient solution method, featuring continuous‐mass transport process (CMTP) by a steady self‐supply way, is shown to keep the growth of semiconductor single crystals continuously stable at a constant growth rate until an expected crystal size is achieved. A significantly reduced full width at half‐maximum (36 arcsec) of the (400) plane from the X‐ray rocking curve indicates a low angular dislocation of 6.8 × 10 6 cm −2 and hence a higher crystalline quality for the CH3 NH3 PbI3 (MAPbI3 ) single crystals grown by CMTP as compared to the conventional inverse temperature crystallization (ITC) method. Furthermore, the CMTP‐based single crystals have lower trap density, reduced by nearly 200% to 4.5 × 10 9 cm −3, higher mobility increased by 187% to 150.2 cm 2 V −1 s −1, and higher mobility–lifetime product increased by around 450% to 1.6 × 10 −3 cm 2 V −1, as compared with the ITC‐grown reference sample. The high performance of the CMTP‐based MAPbI3 X‐ray detector is comparable to that of a traditional high‐quality CdZnTe device, indicating the CMTP method as being a cost‐efficient strategy for high‐quality electronic‐grade semiconductor single crystals. Abstract : A steady self‐supply solution method with a continuously stable growth rate is designed to achieve electronic‐grade high‐quality CH3 NH3 PbI3 perovskite single crystals. The crystal exhibits a low dislocation density, a low trap density, a high mobility, and a high mobility–lifetime product. The charge collection efficiency of a derived MAPbI3 X‐ray detector is comparable to that of a traditional high‐quality CdZnTe device.